VERBAL ADVERBS IN THE WORKS BY FATHER JERONIM VLADIĆ - Šimun Novaković (Hum, 2011)
If we compare formation and syntactical role of verbal adverbs in the past and today we shall notice significant differences. For forming present participle today we use suffix –ći and for perfect participle suffix –vši. In the older grammar books as well in the Franciscan documents we can find suffixes –ć and –v. All four above mentioned suffixes are found in the works by father Jeronim Vladić. There are crucial differences regarding usage of participles attributively. Frequency of using participles attributively in the works by father Jeronim Vladić is directly connected with the norm used for writing a certain work. Usage of participles according to the norm of Zagreb philology school in the works published till 1887 is very frequent. Participles used attributively can be found in later Vladić’s works which were written by the norm of Croatian vukovci, but their usage is less frequent. Here we mostly think of settled terms which we meet in Croatian language today.